Effect of single ethanol administration on behavior and the consumption and preference of ethanol in tame and aggressive rats - R. V. Kozhemyakina; S. G. Shikhevich; A. Cagan; R. G. Gulevich (Вавиловский журнал генетики и селекции)
According to the hypothesis of stress relief, a high level of anxiety or stress may cause greater alcohol consumption and alcohol addiction. However, data obtained with experimental animals do not always confirm this statement. Model strains of Norway rats selected for tame and aggressive attitude to humans are some of the models for investigation of relationships among anxiety, the function of the hypothalamus – pituitary – adrenal (HPA) axis, and predisposition to alcohol addiction. Former studies of tame rats, based on the blood levels of corticosterone and adrenocorticotropic hormone (ACTH) in rest and stress, revealed a decrease of the manifestation of anxiety-like behavior and of the HPA function in comparison to aggressive and unselected rats. This work assesses the preferred consumption of ethanol at various concentrations with free access to ethanol and water (two bottlechoice paradigm) and the effect of acute ethanol administration on the behavior of aggressive and tame male rats in an elevated plus maze. After intraperitoneal alcohol administration, tame and aggressive males showed a reduced number of rearings in the center of the elevated plus maze, but the reduction was statistically significant only in the former. It pointed not only to the absence of an anxiolytic action of 12 % ethanol but also to enhancement of anxietylike behavior in tame rats. After seven-day alcohol withdrawal, tame rats showed signs of deprivation, because the alcohol consumption was greater than before the withdrawal. Thus, the difference between tame and aggressive rats in alcohol consumption varies with alcohol concentration. Aggressive males drank more alcohol than water only at the 2 % concentration. Hence, the hypothesis of stress relief is confirmed only for this concentration.